Biodiesel production from vegetable oil: a review - Abdelrahman, Maha A. A; Yassin, Atif A. A.; Hussein, Ismail Hassan; Mirghani, Mohamed Elwathig Saeed; Karama, Abdallah (Pubtexto Publishers, 2020)
Biodiesel is an alternative, renewable and sustainable source of energy that has become more attractive recently due to environmental concern and diminishing petroleum reserves. This article is focused on reviewing the production of biodiesel from vegetable oil. Biodiesel is produced by Tran’s esterification, catalytic and non-catalytic Tran’s esterification, in addition to assisted techniques such as ultrasonic and microwave-assisted Tran’s esterification. Also, the factors that affect the biodiesel production such as feedstock quality, free fatty acid (FFA) content and moisture content, molar ratio, temperature and agitation speed have been reported. Moreover, the article discussed the biodiesel standard, stability and economics.